Pendekatan Hukum terhadap Isu-isu Lingkungan dalam Pembangunan Berkelanjutan: Tantangan dan Prospek - Dede Kurniawan; Wawan Hermawan; Isep Sunandi; Sabrina Zidni Fadhila (Departement of Mathematics Education, 2021)
The research carried out aims to provide a comprehensive explanation of the challenges and prospects related to legal approaches to environmental problems in sustainable development. This research uses a theoretical approach using secondary data in the form of previous research which strengthens the concepts and theories that are the focus of the problem in this research. By conducting this research, it was found that a legal approach in dealing with environmental problems in sustainable development is an important component in efforts to protect our planet, promote justice, and achieve sustainable development goals. But this approach also highlights a number of complex challenges. Several findings and conclusions from the results of the study regarding the challenges and prospects of this legal approach, namely the challenges of a legal approach to environmental problems and the use of legal innovations such as carbon trading and tax incentives for renewable energy can accelerate the transition to renewable energy. sustainable economy. By working together, communities can play a critical role in creating a more sustainable and equitable future for everyone. The findings obtained provide in-depth insight into the legal complexities and challenges in addressing environmental problems in the context of sustainable development, as well as providing insight into how law can become a more effective tool in protecting the environment in the future.